35 graduands receive CBTM Diploma in UMP and AKEPT collaboration programme - Sakinah, Abdullah; Mimi Rabita, Abdul Wahit (2022)
PAYA BESAR, 8 November 2022 - A total of 35 graduands of the Competency-Based Talent Management Professional (CBTM) 3.0 programme in collaboration with Universiti Malaysia Pahang (UMP) and the Higher Education Leadership Academy (AKEPT) received their diplomas presented by the UMP Vice-Chancellor, Professor Dato’ Ts. Dr. Yuserrie Zainuddin in conjunction with the 17th UMP Convocation Ceremony held at the UMP Sports Complex Hall.